Wage and Price Guidelines and Incomes Policies - Bell, Russell; Fryer, John (Relations industrielles / Industrial Relations, 1967)
The two following papers discuss the views of the Economic Council of Canada and were presented at the Ottawa CIRRI Conference June 1967. Russell Bell is from the Economic Council of Canada and John L. Fryer is from the Canadian Labour Congress.